Genetic by environment interactions and stability of tropical wheat lines in Indonesian medium-plains. (May 2018) - Nur, A; Syahruddin, K; Azrai, M; Farid, M
Abstract: Wheat can adapt well in Indonesia in altitude of 1000-3000 m above sea level (asl) with production ranging 3-5 t/ha. Recently, Indonesia has released several varieties of wheat, but only a few varieties have an adaptation zone under 1000 m asl, which competes to horticultural crops. Therefore, it is important to study the genetic x environment (G x E) interactions and the yield stability of tropical wheat genotypes in the low-medium plains. The study was arranged using Randomized Completed Block Design with 3 replications and 9 genotypes at six locations. The data was analyzed for variant, variant combined and yield stability using STAR programs. The results showed that the environment, genotypes, and interaction of G X E had a highly significant effect on yield and yield components, except for seed weight/spike trait. Further analysis result showed the G4 genotype has significantly greater than the control for trait of days to flower, days to harvest, plant height and a number of panicles/meter. The G1, G4 and G5 genotypes have significantly higher yields than controls. The G4 and G5 genotypes have wide adaptability and G1 genotype has specific adaptability.